Miedos y modos de ver. Sobre la representación del miedo en la narrativa hispanoamericana actual - Pluta, Nina (Romanica Silesiana)
This paper aims at analyzing figures and functions of fear in a significant part of Spanish American fiction at the turn of 21st century. Both as a literary motif that organizes the plot in various kinds of criminal fiction and as a state of mind that seems to be rooted specially in postcolonial societies, the fear and a sense of foreboding is overhelming in fictional universes of Roberto Bolaño, Horacio Castellanos Moya, Juan Villoro, Daniel Sada, Cristina Rivera Garza and many others. A traumatic recent past in the region (military dictatorships, civil wars, drug wars in many countries) partially accounts for this, but this tendency can also be explained by the world democracy crisis and the global growth of insecurity in the beginning of 21st century. The article also takes into consideration the aspects of style, composition and narrative techniques that perpetuate the atmosphere of fear and the notion of an unpunished crime. Key words: Spanish American contemporary fiction, images of fear, detective novel, open-ended fiction